Novel Complex Wave Solutions of the (2+1)-Dimensional Hyperbolic Nonlinear Schrodinger Equation - Durur, Hulya; Ilhan, Esin; Bulut, Hasan (Mdpi, 2020)
This manuscript focuses on the application of the(m+1/G ')-expansion method to the (2+1)-dimensional hyperbolic nonlinear Schrodinger equation. With the help of projected method, the periodic and singular complex wave solutions to the considered model are derived. Various figures such as 3D and 2D surfaces with the selecting the suitable of parameter values are plotted.
Keywords: the (m+1/G ')-expansion method; the (2+1)-dimensional hyperbolic nonlinear Schrodinger equation; periodic and singular complex wave solutions; traveling waves solutions